The effect of defoliation of silver birch (Betula pendula R.) by gypsy moth (Lymantria dispar L.) on the composition and content of chemical compounds in its leaves under anthropogenic influence - E.V. Koltunov (Учёные записки Казанского университета: Серия Естественные науки)
Periodic outbreaks of insects cause significant ecological and economic damage to forests. For this reason, it is especially important to study the biochemical mechanisms underlying entomoresistance, either induced or constitutive, in forest stands. The purpose of the study is to investigate the biochemical specificity of these types of entomoresistance using the method of high-performance liquid chromatography (HPLC). It has been shown for the leaves of the defoliated stands that 59% of fractions increased in content, while the content of 36% of fractions decreased and 4.9% of fractions exhibited no changes in their concentration. A total of 20 compounds have been identified. It has been observed that the content of the identified compounds under the effect of defoliation increased (55%), decreased (40%), or did not change (5%). The first group of compounds includes phenol glycosides (arbutin, salicin), flavonoids (isoquercitrin, luteolin, quercetin, apigenin, myricetin, kaempferol), hydroxycarboxylic acids (gallic acid), hydroxycinnamic acids (caftaric acids), and vitamins (ascorbic acid). Previously, we revealed the composition of phenolic compounds determining constitutive entomoresistance. The comparative analysis of their composition and the identified compounds of induced entomoresistance has shown a very close similarity. Therefore, it can be suggested that the parameters of induced and constitutive entomoresistance in silver birch are determined by the same phenolic compounds.